2019
DOI: 10.2807/1560-7917.es.2019.24.48.1900693
|View full text |Cite
|
Sign up to set email alerts
|

Current experiences of accessing and using HIV pre-exposure prophylaxis (PrEP) in the United Kingdom: a cross-sectional online survey, May to July 2019

Abstract: The 2019 online pre-exposure prophylaxis (PrEP) user survey in the United Kingdom was conducted to assess HIV PrEP access, and user characteristics. One in five respondents continued experiencing difficulties accessing PrEP; users were almost exclusively gay or bisexual men at high risk of HIV. The majority obtained PrEP through health service clinics and rated PrEP positively. High STI rates were reported among users. Renal and sexual health checks are advised for those sourcing PrEP privately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 5 publications
5
51
0
Order By: Relevance
“…Consistent with previous studies targeting MSM PrEP users [ 15 , 16 , 17 , 18 , 19 ], our participants reported a high and stable prevalence of sexual risk behaviors (e.g., CAI, multiple male sex partnerships and SDU) over the study period. According to the CDC’s clinical practice guideline [ 21 ], they should receive STI testing at least every three months.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies targeting MSM PrEP users [ 15 , 16 , 17 , 18 , 19 ], our participants reported a high and stable prevalence of sexual risk behaviors (e.g., CAI, multiple male sex partnerships and SDU) over the study period. According to the CDC’s clinical practice guideline [ 21 ], they should receive STI testing at least every three months.…”
Section: Discussionsupporting
confidence: 90%
“…As PrEP use became more common, studies suggested that many MSM reduced condom use after initiating PrEP. The prevalence of STI among MSM PrEP users ranged from 14.2 to 50.6%, while the STI incidence in this group was as high as 34.2–119.8 per 100 person-year [ 15 , 16 , 17 , 18 , 19 ]. A recent meta-analysis suggested that PrEP use was associated with a 24% increase in the prevalence of STI and a 59% increase in the risk of rectal STI among users [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting result of the present study is that PrEP’s affordability and accessibility determine the will to use it. A survey carried out in England in 2019 showed that 30.9% of users gained PrEP throughout the Internet [ 41 ]. This could be due to the fact that, in England, online purchasing of PrEP has been available since 2015 under the supervision of the National Health System.…”
Section: Discussionmentioning
confidence: 99%
“…However, we anticipate that individuals are likely to switch from private to publicly funded PrEP as access improves over time. In addition, some supplementary data exist from community-based surveys to help estimate the proportion of PrEP users who source this privately [11]. HIV: human immunodeficiency virus; PrEP: pre-exposure prophylaxis; Q: calendar quarter.…”
Section: Measure 2: Number Of Attendees In the Reporting Quarter Who mentioning
confidence: 99%